Evaluation of physicians’ opioid prescribing practices, attitudes, and interactions with other healthcare professionals in optimizing opioid prescribing in Pakistan - Arshad, Hafsa; Gillani, Ali Hassan; Arshed, Muhammad; Fang, Yu (Frontiers in Pharmacology, 2025)
BackgroundThe community is facing an imminent opioid crisis, with prescription opioids playing a significant role. We conducted a study to assess physicians’ experience with opioid prescribing, their reported degree of confidence in prescribing, any adverse events that occurred, and their interactions with other healthcare providers regarding opioid medication.MethodsFrom October 2023 to March 2024, physicians in three cities in Punjab, Pakistan, participated in a physical, cross-sectional survey based on questionnaires. A 56-item questionnaire was distributed to physicians working in both public and private hospitals. The demographics and other items were evaluated using descriptive statistics, and the associations between knowledge, attitude, and concerns were tested using the Spearman rho test. The statistical analyses were conducted using SPSS.ResultsOf the 1,009 physicians contacted for the study, 816 (80.9%) answered and completed the survey. The average age of these physicians was 38 years. More than half of the respondents were men, accounting for 58.8% of the total, and an equal proportion of respondents, 56.9%, were from government hospitals. Most individuals (92.2%) were knowledgeable about the possible hazards and negative consequences linked to opioid therapy, and almost as many were aware of the risk factors associated with opioid misuse (90.2%). The majority of physicians displayed a favorable attitude, with 54.9% expressing confidence in their ability to detect patients with a strong propensity for addiction. The majority of physicians expressed worries regarding the use and management of opioids, with only 11.8% indicating no concern about legislation and 7.8% indicating no concern about overdose and abuse. Half (51.0%) of the participants never prescribed opioids, while 5.9% had a tendency to regularly prescribe them to patients. There is a strong positive linear correlation between knowledge and attitude, knowledge and concerns, and attitude and concerns.ConclusionPrescribers were well aware of risk factors and abuse-related problems and showed a good attitude and positive concerns regarding opioid use. The practices are moderately appropriate and can be further refined by incorporating the proper guidelines and legislations in the curricula.